2020
DOI: 10.1177/0034355220922607
|View full text |Cite
|
Sign up to set email alerts
|

Employability With Mental Illness: The Perspectives of Employers and Mental Health Workers

Abstract: Having prior contact with people with mental illness in the workplace can lead to an improvement in employers’ attitudes toward this group. However, there is currently a lack of instruments to measure attitudes toward the employability of people with mental illness. The overall aim of this study was to develop a Spanish scale of attitudes toward the employability of people with mental illness (CEPEM) and obtain preliminary data regarding its psychometric properties. Ninety-four items from three content domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although interviewees did identify bad relationships at work as another important barrier, they never actually explained them as work discrimination for being treated unfairly in the workplace because of having a psychiatric disability. However, labor force discrimination of people with mental illness is a barrier that has been reviewed for several years [6,[37][38][39] and some recent studies have shown that experiences of discrimination at work limit the improvement of selfesteem for people with mental illness [40]. Moreover we have to consider that negative work experiences facilitate negative expectations regarding future work opportunities, and that people could easily decide stay out of the work market because they anticipate work discrimination [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although interviewees did identify bad relationships at work as another important barrier, they never actually explained them as work discrimination for being treated unfairly in the workplace because of having a psychiatric disability. However, labor force discrimination of people with mental illness is a barrier that has been reviewed for several years [6,[37][38][39] and some recent studies have shown that experiences of discrimination at work limit the improvement of selfesteem for people with mental illness [40]. Moreover we have to consider that negative work experiences facilitate negative expectations regarding future work opportunities, and that people could easily decide stay out of the work market because they anticipate work discrimination [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars suggested that job stress associated with mental health stigma have focused on global levels (DeVries and Wilkerson, 2003), formal economy (Elraz, 2018) and among informal men workers (Dozier, 2017). Some studies demonstrated mental health stigma (Fox et al , 2018; Lettieri et al , 2021) as a broad understanding of individual practices across the field.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we used an instrument recently developed in Spain to measure the attitudes toward the employability of people with mental illness (CEPEM: Questionnaire about the employability of people with mental disorders). This scale was previously used with employers and mental health professionals (Lettieri, Soto‐Pérez, et al., 2021 ), providing the first explorative results and showing acceptable psychometric properties. The last version of the scale, after being checked for internal consistency, provided 33 items distributed into the content spheres of attitudes toward (1) people with mental illness, (2) their employability, and the (3) socio‐economic impact on the company.…”
Section: Methodsmentioning
confidence: 99%
“…Research on the attitudes of mental health professionals toward the employability of people with mental illness, as well as the stakeholders involved in promoting and supporting employment for these people, provide important insight for addressing this issue. Nonetheless, while there are reports that detail the points of view of employers (Hand & Tryssenaar, 2006 ; Jansson & Gunnarsson, 2018 ; Lettieri, Díez, et al., 2021 ; Mangili et al., 2011 ; Ozawa & Yaeda, 2007 ; Unger, 2002 ), there are not that many focusing on the attitudes and perceptions of mental health professionals toward the employability of people with mental illness (Fleming et al., 2019 ; Gladman et al., 2015 ; Lettieri, Soto‐Pérez, et al., 2021 ). The role of these professionals is crucial for helping people not only medically but also to help them achieve a better quality of life through the positive experience of obtaining a job and their subsequent recovery (Bertilsson et al., 2015 ; Gladman et al., 2015 ; Porter, et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation